2014
DOI: 10.1128/iai.00534-13
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Mediates Enterohemorrhagic Escherichia coli O157:H7-Induced Attaching and Effacing Lesions

Abstract: Enterohemorrhagic Escherichia coli serotype O157:H7 causes outbreaks of diarrhea, hemorrhagic colitis, and the hemolyticuremic syndrome. E. coli O157:H7 intimately attaches to epithelial cells, effaces microvilli, and recruits F-actin into pedestals to form attaching and effacing lesions. Lipid rafts serve as signal transduction platforms that mediate microbe-host interactions. The aims of this study were to determine if protein kinase C (PKC) is recruited to lipid rafts in response to E. coli O157:H7 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Cani and colleagues previously found that prebiotics increased the expression of both ZO-1 and occludin in mice via a microbe-dependent mechanism21, but the possibility of direct non-microbial mechanism has also been suggested23. We previously identified that atypical PKC isoforms are involved in the signaling responses to EHEC24, we extend these findings by now showing PKC signaling can also be triggered by exposure to dietary prebiotics to alter epithelial barrier and TJ function. This observation was validated through PKC loss-of-function experiments, which abolished the protective effects of prebiotics on epithelial barrier integrity.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Cani and colleagues previously found that prebiotics increased the expression of both ZO-1 and occludin in mice via a microbe-dependent mechanism21, but the possibility of direct non-microbial mechanism has also been suggested23. We previously identified that atypical PKC isoforms are involved in the signaling responses to EHEC24, we extend these findings by now showing PKC signaling can also be triggered by exposure to dietary prebiotics to alter epithelial barrier and TJ function. This observation was validated through PKC loss-of-function experiments, which abolished the protective effects of prebiotics on epithelial barrier integrity.…”
Section: Discussionsupporting
confidence: 69%
“…Caco-2Bbe1 cells, a differentiated Caco-2 subclone which attains faster confluency, were purchased from American Type Culture Collection and grown using cell culture conditions as previously described824. Cells were harvested with trypsin-EDTA and seeded onto 6.5-mm Transwell filter supports (~1 × 10 5 cells/insert, Corning, Mississauga, Canada) and maintained for 3–4 d until TER reached >800 Ω cm −2 measured using chopstick electrodes (Millipore, Etobicoke, Canada)939.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…coli is capable of determining the deamidation of Rho GTPases through the production of CNF-1 (Cytotoxic Necrotizing Factor-1) [ 65 ]. Previous studies suggested that the ability of E. coli to raise intracellular calcium levels and generate diacylglycerol (DAG) led to the proposal that EPEC activates calcium- dependent protein kinases, including protein kinase C (PKC), in host epithelia [ 66 ]. It has been also reported that activation of PKC results in up-regulation of iPLA 2 ß expression that leads to activation of RhoA/Rho kinase/CPI-17 signalling [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, ANXA6 can negatively control the EGFR/Ras pathway through binding to p120GAP and PKCα [76]. Both EPEC and EHEC infections can modulate the host cytoskeleton by future science group www.futuremedicine.com activating PKCα and recruiting PKC to form adhesion pedestals via functionally intact lipid rafts [77][78][79], but the precise factor that mediates this event is unknown. PKC activation is also controlled by the PI3K/Akt signaling pathway, on which the EPEC depends to escape phagocytosis by host cell macrophages [78,79].…”
Section: Discussionmentioning
confidence: 99%